ARTISTIC CONCEPT OF FEMALE CHARACTERS IN PROSE OF MARKO VOVCHOK AND TONI MORRISON - Iermak, L. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the chronotope factor of perception of personal and social factors by the female characters in prose of MarkoVovchok and Toni Morrison. We analyze the importance of chronotope in creating images of women in Toni Morrison’s novel "Sula", "Beloved" and in Marko Vovchok’s prose – «Folk Stories», «College Girl», «Three fates» and «Marusya». Space and time are viewed in the social and psychological context (dissonance of serfdom-master-society), and on household level (epoch-house-slave-society).